2023
DOI: 10.1186/s12931-023-02331-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NLRP3 inflammasome in lung epithelial cells triggers radiation-induced lung injury

Abstract: Background Radiation-induced lung injury (RILI) is the most common and serious complication of chest radiotherapy. However, reported radioprotective agents usually lead to radiation resistance in tumor cells. The key to solving this problem is to distinguish between the response of tumor cells and normal lung epithelial cells to radiation damage. Methods RNA-Seq was used to recognize potential target of alleviating the progression of RILI as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…To date, efforts to develop targeted drugs for sites of ionizing radiation damage, such as NLRP3 in ammasome [32,33], have yielded little bene t and therapeutic options for clinical treatment have not been studied in detail [34]. However, none of these treatment options has been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…To date, efforts to develop targeted drugs for sites of ionizing radiation damage, such as NLRP3 in ammasome [32,33], have yielded little bene t and therapeutic options for clinical treatment have not been studied in detail [34]. However, none of these treatment options has been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…γ radiation not only activates the NLRP1 and NLRP3 complexes in microvascular endothelial cells but also activates caspase-1 directly [ 23 ]. In lung epithelial cells, radiation-induced NLRP3 activation depends on glycolysis-associated reactive oxygen species (ROS) accumulation [ 24 ]. In addition, ROS involvement in radiation-induced NLRP3 activation has also been found in other cells [ 25 ], and irradiation-induced NLRP3 activation enhances lung hypersensitivity with more monocyte’s infiltration [ 25 ].…”
Section: Radiation Regulates Pyroptosis Through Various Mechanismsmentioning
confidence: 99%
“…Of note, damaged alveolar epithelial cells and vascular endothelial cells also secrete various cytokines, including tumor necrosis factors (TNF-α) involved in local injury and inflammatory response, transforming growth factor β-1 (TGF-β1) that promotes tissue repair and organ fibrosis, platelet-derived growth factor (PDGF), interleukins (IL-1β, IL-6, IL-8, IL-10), and monocyte chemotactic peptides ( 32 , 44 , 45 ). Among them, some studies have shown that TGF-β1-based CRISPR/Cas9 gene therapy improves lung tissue pathological damage, reduces the secretion and expression of inflammatory factors, and ultimately inhibits the progression of radiation fibrosis ( 46 ).…”
Section: Pathogenesis Of Rilimentioning
confidence: 99%